Targeting un-MET needs in advanced non-small cell lung cancer. (February 2022) - Coleman, Niamh; Harbery, Alice; Heuss, Sara; Vivanco, Igor; Popat, Sanjay
Highlights: Lung cancer classification has been radically transformed in recent years as genomic profiling has identified multiple novel therapeutic targets, including MET exon 14 ( MET ex14) alterations and MET amplification. Utilizing targeted therapies in patients with molecularly-defined NSCLC leads to remarkable objective response rates and improved progression-free survival, however, acquired resistance is inevitable. METex14 has recently established an actionable oncogenic-driver in non-small cell lung cancer (NSCLC). Several recent phase II trials have confirmed that MET ex14 NSCLC can be treated effectively with MET kinase inhibitors, such as capmatinib and Tepotinib, which are now FDA-approved agents. There remains scope for improvement as response rates for many MET TKIs are modest compared to the activity of targeted therapy in other oncogene-driven lung cancers, where ORRs are more consistently greater than 60%. There have significant advancements in the field of MET inhibition in NSCLC, however, challenges remain: the landscape of resistance mechanisms to MET TKIs is not yet well characterized, and there may be intrinsic and acquired resistance mechanisms that require further characterization to enable increased MET TKI activity. Abstract: Lung cancer classification has been radically transformed in recent years as genomic profiling has identified multiple novel therapeutic targets including MET exon 14 ( MET ex14) alterations and MET amplification. Utilizing targeted therapies in patients with molecularly-defined NSCLC leads to remarkable objective response rates and improved progression-free survival. However, acquired resistance is inevitable. Several recent phase II trials have confirmed that MET ex14 NSCLC can be treated effectively with MET kinase inhibitors, such as crizotinib, capmatinib, tepotinib, and savolitinib. However, response rates for many MET TKIs are modest relative to the activity of targeted therapy in other oncogene-driven lung cancers, where ORRs are more consistently greater than 60%. In spite of significant gains in the field of MET inhibition in NSCLC, challenges remain: the landscape of resistance mechanisms to MET TKIs is not yet well characterized, and there may be intrinsic and acquired resistance mechanisms that require further characterization to enable increased MET TKI activity. In this review, we overview MET pathway dysregulation in lung cancer, methods of detection in the clinic, recent clinical trial data, and discuss current mechanisms of TKI resistance, exploring emerging strategies to overcome resistance.